2008
DOI: 10.1002/jemt.20567
|View full text |Cite
|
Sign up to set email alerts
|

Nidogens—Extracellular matrix linker molecules

Abstract: Nidogens/entactins are a family of highly conserved, sulfated glycoproteins. Biochemical studies have implicated them as having a major structural role in the basement membrane. However despite being ubiquitous components of this specialized extracellular matrix and having a wide spectrum of binding partners, genetic analysis has shown that they are not required for the overall architecture of the basement membrane. Rather in development they play an important role in its stabilization especially in tissues un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
4
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 84 publications
(98 reference statements)
2
108
4
2
Order By: Relevance
“…This is despite the follicular basal lamina of primordial follicles having all six collagen type IV chains and at least the laminin chains a-1, b-2 and g-1 . Nidogens are universally produced by mesenchymal cells even when present as a component of epithelial basal lamina (Ho et al 2008). However, in the present study, we have shown that the granulosa cells express NID1 and -2, with NID2 mRNA levels being an order of magnitude greater than NID1.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This is despite the follicular basal lamina of primordial follicles having all six collagen type IV chains and at least the laminin chains a-1, b-2 and g-1 . Nidogens are universally produced by mesenchymal cells even when present as a component of epithelial basal lamina (Ho et al 2008). However, in the present study, we have shown that the granulosa cells express NID1 and -2, with NID2 mRNA levels being an order of magnitude greater than NID1.…”
Section: Discussioncontrasting
confidence: 55%
“…NID1 and -2 can bind laminin g-1, COL4 and HSPG2, thus cross-linking these components makes the basal lamina more rigid. They have overlapping functions, but are not identical as NID2 has lower affinity for laminin and can bind endostatin, whereas NID1 does not (Ho et al 2008). During follicular development, these molecules are differentially regulated and are absent from the follicular basal lamina in the primordial follicles but appear at the early antral stage (McArthur et al 2000, Irving-Rodgers & Rodgers 2006.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Therefore, NKp44-NID1 interactions are likely to occur in tissues, namely in the mucosae, which contain both NK cells and ILC3, expressing NKp44 receptor. 59-61 The role of NKp44 in regulating the function of these cells has not been clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…70 In addition, NID1 can interact with different BM/ECM proteins including laminin, collagen type IV, and perlecan. 57,58 Thus, it is possible that the tissue microenvironment and the molecular context may further influence the functional outcome of the NID1-NKp44 interaction. The ability of NKp44 to recognize NID1 glycoprotein both in denatured and native conditions indicates that NKp44 may bind to a linear epitope.…”
Section: Discussionmentioning
confidence: 99%
“…Nidogen-1 and -2 are secreted proteins that stabilize the BM by interacting with other ECM proteins such as laminin, collagen IV, perlecan, and fibulin. 19 ISH on wild-type retinas showed that Nidogen-2 mRNA was transcribed at highest levels in tip cells and at much lower levels in the rest of the vasculature, including stalk cells (Figure 2A-B). Comparison with DLL4 ϩ/Ϫ retinas showed that, as expected from the microarray data, Nidogen-2 mRNA was expressed over a wider area in DLL4 ϩ/Ϫ , with no obvious difference in expression levels between tip and stalk cells (Figure 2C-D).…”
Section: Molecules Involved In Ecm Formationmentioning
confidence: 99%